PELATIHAN DESAIN PRODUK INDUSTRI CREATIVE CARD DENGAN MEDIA DIGITAL DI DESA KEROBOKAN KAJA KABUPATEN BADUNG PROVINSI BALI - Jayantini, I Gusti Agung Sri Rwa; Tustiawati, Ida Ayu Mela; Caskara, I Gde Agoes Caskara Surya; Cahyanti, Ni Kadek Ayu Rina Dwi (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
This community service program centers on the activities of empowering youth groups in response to the COVID-19 pandemic’s impacts on economy. It is intended to target those experiencing the loss of job due to company’s manpower reduction. The program is specifically conducted to the youth group in the village of Kerobokan Kaja, which is located in Badung regency, Bali province. The focus of activities is on the training of making digital design for the products that the participants want to sell and to widen the youth group’s knowledge on the features of online marketing. The participants were involved in the activity of both online meeting and face to face consultation with the strict health protocols since the program is conducted during the pandemic time. The method applied here was the combination presentation, tutorial, discussion and practice. They joined actively in the sharing of tips and tricks to make a digital design using Canva application and of understanding marketing strategies in the marketplace. Despite the limited access of interaction due to the pandemic, the program had given a significant contribution to the participants because they could apply their new knowledge as the alternative to get income while facing the loss of job. Kata kunci: community service program, digital design, online marketing